A STUDY ON THE MORPHOLOGICAL AWARENESS OF THE SECOND-YEAR STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Khairumi, Nurul; Delfi, Syofia; Novitri, Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The objective of the present study was to find out the morphological awareness of the second-year students of English Study Program FKIP Universitas Riau. It was descriptive research that involved 35 second-year students as the sample by using cluster random sampling. The data were collected by giving a Morphological Awareness Test (MAT) adapted from Apel and Lawrence (2011) to see their morphological awareness in terms of the syntactic aspect: Derivations and Inflections. For analyzing the data, the descriptive statistics (mean score and standard deviation) were calculated and the students’ individual scores were grouped into some levels of morphological awareness. It was revealed that the second-year students of English Study Program FKIP Universitas Riau who participated in the present study had low level of morphological awareness (M=49.71). They slightly performed better in Inflections part than in Derivations part. Thus, it is recommended to conduct a further research to investigate the motives behind the students’ low performance on morphological awareness.Key Words: Morphology, Morphological Awareness